If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + 9) + 2(6x + -1) = 360 Reorder the terms: 2(9 + 2x) + 2(6x + -1) = 360 (9 * 2 + 2x * 2) + 2(6x + -1) = 360 (18 + 4x) + 2(6x + -1) = 360 Reorder the terms: 18 + 4x + 2(-1 + 6x) = 360 18 + 4x + (-1 * 2 + 6x * 2) = 360 18 + 4x + (-2 + 12x) = 360 Reorder the terms: 18 + -2 + 4x + 12x = 360 Combine like terms: 18 + -2 = 16 16 + 4x + 12x = 360 Combine like terms: 4x + 12x = 16x 16 + 16x = 360 Solving 16 + 16x = 360 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 16x = 360 + -16 Combine like terms: 16 + -16 = 0 0 + 16x = 360 + -16 16x = 360 + -16 Combine like terms: 360 + -16 = 344 16x = 344 Divide each side by '16'. x = 21.5 Simplifying x = 21.5
| y=9x+4 | | x+19=27 | | 5x^2-3x+40=0 | | 3b-2a=9 | | 20-4c=-68 | | X(x+2)-2(x+2)= | | 6(3x-1)-2x=2(2x-5)-8 | | 5x+3=7x | | q=7(p-2)+3 | | 5w+30=2w+36 | | y=4.7x^2+4.5x+40 | | 6f=120 | | 2y-7=-1y-2y | | 6n-12=3(2n-4) | | 12t^2-4t=-3 | | 2[s+3(s-1)]=18 | | 3a-2b=9 | | 12d=48 | | 8x-6=3x-26 | | -111+2s=9 | | 6n-12=(2n-4) | | 5x-12=7x+8 | | 2a-24-31=5a | | x-1.75=24 | | 15x+9=12x | | 6(-9x-7)=5(12x-12) | | 37-18-(8x)=67 | | 18=2k-4 | | 4x-10=-4x+21 | | 18=2k-4 | | 2(y+p)=3p+s | | 37-18-8x-6=x |